CVnCoV and CV2CoV protect human ACE2 transgenic mice from ancestral B BavPat1 and emerging B.1.351 SARS-CoV-2 - Donata Hoffmann (Nature Portfolio, 2021)
Emerging SARS-CoV-2 variants with mutations in the spike protein raise concerns regarding vaccine efficacy. Here, the authors show that two spike encoding mRNA vaccines in preclinical and clinical development protect human ACE2 mice from the B.1.351 variant of concern and ancestral B BavPat1.